2021
DOI: 10.1038/s41467-021-26576-2
|View full text |Cite
|
Sign up to set email alerts
|

rRNA biogenesis regulates mouse 2C-like state by 3D structure reorganization of peri-nucleolar heterochromatin

Abstract: The nucleolus is the organelle for ribosome biogenesis and sensing various types of stress. However, its role in regulating stem cell fate remains unclear. Here, we present evidence that nucleolar stress induced by interfering rRNA biogenesis can drive the 2-cell stage embryo-like (2C-like) program and induce an expanded 2C-like cell population in mouse embryonic stem (mES) cells. Mechanistically, nucleolar integrity maintains normal liquid-liquid phase separation (LLPS) of the nucleolus and the formation of p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 92 publications
3
31
0
1
Order By: Relevance
“…We found that iPol I ESCs or 2C-like cells do not display typical nucleolar stress markers, and iPol I ESCs still activate Dux in the absence of p53, albeit with slightly reduced levels. In contrast, p53 activation upon longer or more severe nucleolar stress in ESCs may also significantly contribute to Dux activation ( Sun et al 2021 ; Yu et al 2021 ). Instead, our data on acute, milder nucleolar disruption agree with previous nucleolar gene positioning studies, which demonstrated in yeast that an ectopic rDNA repeat can silence its chromosomal region ( Zuccotti et al 2005 ) and that 5S rDNA sequences are sufficient to induce nucleolar association and silencing of a reporter gene in ESCs ( Fedoriw et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that iPol I ESCs or 2C-like cells do not display typical nucleolar stress markers, and iPol I ESCs still activate Dux in the absence of p53, albeit with slightly reduced levels. In contrast, p53 activation upon longer or more severe nucleolar stress in ESCs may also significantly contribute to Dux activation ( Sun et al 2021 ; Yu et al 2021 ). Instead, our data on acute, milder nucleolar disruption agree with previous nucleolar gene positioning studies, which demonstrated in yeast that an ectopic rDNA repeat can silence its chromosomal region ( Zuccotti et al 2005 ) and that 5S rDNA sequences are sufficient to induce nucleolar association and silencing of a reporter gene in ESCs ( Fedoriw et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the mESC to 2CLC transition, a lower TAD strength and TAD insulation have been observed [39]. Consistent with this is the disruption of chromatin organization by the depletion of CCCTC-binding factor (CTCF)/Cohesin or by culturing with CX-5461 upregulate Dux expression and promote a 2-cell-like program [13,14]. It is worth noting that the attenuation of H3K9me3 and H3K27me3 in CX-5461-treated cells is associated with the reinforcement of a repressed chromatin state [65].…”
Section: D Genome Conformationmentioning
confidence: 73%
“…Thus, differences in ribosome biogenesis can cause specialized mRNA subsets to be translated, which indirectly determine cell identity. Recent studies indicate that the inhibition of rRNA biogenesis can promote the state transition from ESCs to 2CLCs [11,13]. CX-5461, an RNA Pol I inhibitor, can decrease rRNA biogenesis and disrupt the nucleolar integrity and formation of peri-nucleolar heterochromatin (PNH).…”
Section: Rrna Biogenesis Pathwaymentioning
confidence: 99%
See 2 more Smart Citations